2016
DOI: 10.1097/ijg.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Exercises on Ocular Physiology: A Review

Abstract: Sport has been known to be one of the most important factors in preventing cardiovascular disorders; some studies suggest its role in preventing neurodegenerative diseases. This review discusses the results of various studies regarding the effects of physical exercises on intraocular pressure (IOP), myopia, certain physical parameters of the eye, ocular blood flow, and retinal electrical function. Although dynamic exercises are known to reduce IOP from 1.2 to 5.9 mm Hg only for a short period of time, uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 117 publications
2
70
0
6
Order By: Relevance
“…Ethnic differences in ocular anatomies, such as anterior chamber dimension and axial length, are well documented (Wylęgała ), and recent studies have also shown differences in physiology. One study observed lower retrobulbar flow in people of African descent than in those of European descent and suggested that this difference may be because of higher glaucoma rate in African population (Kaskan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic differences in ocular anatomies, such as anterior chamber dimension and axial length, are well documented (Wylęgała ), and recent studies have also shown differences in physiology. One study observed lower retrobulbar flow in people of African descent than in those of European descent and suggested that this difference may be because of higher glaucoma rate in African population (Kaskan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent evidence suggests a positive role of physical exercise on the retinal physiology. 21, 31 In this study, the lack of significant ocular structural differences between the two groups may be related to experimental factors. For example, although our subjects exercised six days per week, the duration of each training session may have not been long enough to effectively counteract the cephalad fluids shift induced by head-down-tilt and to reduce the amount of peripapillary retinal thickening post bed rest.…”
Section: Discussionmentioning
confidence: 79%
“…Although several studies have investigated the relationship between exercise and IOP and/or glaucoma [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], there are scant data about exercise and OBF parameters. Investigating exercise-induced changes in OBF-related parameters in treated patients with POAG, we found a significant increase in both OPA and OPP values immediately after exercise, which persisted for at least 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between glaucoma and physical activity has been previously investigated by several studies [13][14][15][16][17][18][19][20]. These reports have evaluated the effect of different aerobic and anaerobic exercises on IOP [13][14][15][16][17][18][19][20]. In general, a modest and transient IOP decrease has been documented following exercise.…”
Section: Introductionmentioning
confidence: 99%